DISTRIBUTION OF AGAINST ASSETS AND DETERMINATION OF CHILDREN'S RESPONSIBILITY DUE TO DIVORCE: PEMBAGIAN HARTA GONO-GINI DAN PENETAPAN HAK ASUH ANAK AKIBAT PERCERAIAN - Carissa Christiana (SOSIOEDUKASI, 2023)
This research was conducted with the aim of finding out how the dividend of property due to divorce according to the Marriage Law and how to determine custody of children due to divorce. By using the normative juridical research method, the following conclusions are: 1. Distribution of property due to divorce based on the provisions of Article 36 of the Marriage Law, husband and wife can act with the consent of both parties. 2. Determination of custody of children due to divorce according to Presidential Instruction No. 1 of 1991, for children who are not yet mature or not yet 12 (twelve) years of age are the rights of the mother. Meanwhile, for adult children, it is up to the child to choose between the father and mother as the holder of the child's rights. Or according to the judge's consideration based on the condition of the wife's and husband's behavior in raising children. The court ruling on child custody does not sever the blood relationship between the child and the biological parents and does not eliminate the obligation of both parents to support their child.